A plant CLE peptide and its fungal mimic promote arbuscular mycorrhizal symbiosis via CRN-mediated ROS suppression - Sagar Bashyal; Hasani Everett; Suzanne Matsuura; Lena Maria Müller (Proceedings of the National Academy of Sciences, 2025)
CLAVATA3/EMBRYO SURROUNDING REGION-related (CLE) peptides have emerged as key regulators of plant–microbe interactions, including arbuscular mycorrhizal (AM) symbiosis. Here, we identify Medicago truncatula CLE16 as a positive regulator of AM symbiosis. MtCLE16 is expressed in root cells colonized by AM fungi (AMF) and its overexpression within colonized tissues increases arbuscule abundance by finetuning their growth and lifespan. Functional and transcriptomic analyses reveal that MtCLE16 acts via the M. truncatula pseudokinase CORYNE (MtCRN) and suppresses the accumulation of reactive oxygen species (ROS) in roots, thereby attenuating immune responses and promoting root colonization by mutualistic AM fungi. Notably, AMF also express MtCLE16-like peptides. We show that the Rhizophagus irregularis MtCLE16-like peptide, RiCLE1, also attenuates ROS and promotes AMF colonization via MtCRN. This finding suggests that RiCLE1 can interfere with the MtCLE16-MtCRN signaling module of host roots to benefit the fungus. Our research uncovers a functional mechanism underpinning cross-kingdom signaling and molecular mimicry in mutualistic plant–microbe interactions.